Habitat Selection by Northern Bobwhite Broods in Pine Savanna Ecosystems - William E. Palmer; D. Clay Sisson; Shane D. Wellendorf; Allan M. Bostick III; Theron M. Terhune; Tyson L. Crouch (National Quail Symposium Proceedings, 2017)
Habitat for northern bobwhite (Colinus virginianus) broods is a critical component of bobwhite management. Research within pine (Pinus spp.) savannas has provided contradictory results regarding the value of macro-habitats with studies demonstrating selection for annually-disked fallow fields and others showing avoidance of fields and selection for burned pine savannas. Field establishment (up to 30% of a property) is a published management recommendation for bobwhites in pine savannas but there are significant annual costs with fallow-field management; information on factors that influence habitat selection by broods can improve management recommendations and facilitate weighing costs/benefits. We examined 2nd and 3rd order habitat selection by 466 broods on 3 sites during 1999–2009. All sites had similar macro-habitats (e.g., pine savanna, fallow fields, hardwood drains) but differed in soil characteristics and species composition of ground vegetation. Annually-disked fields were preferred by broods in most years on sites with predominantly grass and hardwood scrub ground vegetation. Rainfall mediated use of hardwood drains and burned upland pine savannas; hardwood drains were used more during droughts whereas burned pine savannas were used more with increased rainfall. Burned upland pine savanna was preferred on higher fertility sites in 9 of 10 years at the 3rd order level, fields were avoided or used according to availability in 8 of 10 years, and drains were avoided. Managers should consider how soil, weather, and vegetation community in pine savannas influences habitat use by bobwhite broods when identifying the value of different macro-habitats. Field establishment may or may not provide brood habitat depending on site.
Keywords: broods; chicks; Colinus virginianus; fields; fire; habitat use; northern bobwhite; pine; savanna